Konstruktivisme, konstruksionisme en maatskaplike werk - Plessis, M. J. M. du (Koers, 2000)
Constructivism, constructionism and social workIn this article the constructivistic framework of reasoning is illustrated with reference to the premises of the structure determinism of Maturana, Kelly's personality constructs theory, and the radical constructivism as developed by Von Glasersfeld. Proceeding to the constructivistic frame of thought that reality is created by each individual with reference to particular internal processes (specifically cognitive processes), constructionism indicates, according to the social construct theory, that the interaction between individuals is responsible for the process of reality creation. The core of the frameworks of reasoning involves that reality is not created by the individual or individuals, and that, therefore not only one objective reality exists, but in fact a range of subjective realities - realities that are continually adapted by means of a process of evolution. As the individual is exposed to new experiences, he attaches new unique meanings to it, and this continually creates another reality. This view implies specific implications for the profession of Social Work. For example, final and objective diagnoses about persons, families, groups or communities cannot be made, as such diagnoses are based on a subjective reality created by a social worker in a certain situation. Indeed, there is no objective reality against which those concerned could be measured in order to come to a conclusion. Further, constructivism and constructionism imply that the social worker departs from a position of "not-knowing". He is therefore not the only skilled person, but seeks, together with the client, new realities that could contain the solution of the problems of the client.